SIMULTANEOUS ASSAYS OF METFORMIN HCL AND GLIBENCLAMIDE MIXTURE USING TWO ANALYTICAL METHODS OF SPECTROPHOTOMETRY - BACHRI, MUCHLISYAM (International Journal of Applied Pharmaceutics, 2019)
Objective: Area Under Curve method (AUC) and the Multiple Wavelength Spectrophotometric (MWS) method are practice and simple methods for simultaneous assays of Metformin HCl and Glibenclamide on the tablet dosage form. Methods: The AUC method is measured for the absorption spectrum with a concentration 4 mg/l Metformin HCl by calculating the area spectrum at wavelength 230-240 nm and the absorption spectrum with a concentration 8.7 mg/l Glibenclamide by calculating the area at wavelength 225-235 nm. The MWS by determining the absorption spectrum and the five wavelength points for the absorption value at 225 nm, 229.4 nm, 236.6 nm, 233 nm, and 243 nm and calculated using matrix operations. Results: The validation test of the AUC method for Metformin HCl obtained accuracy = 99.35%, linearity = 0.9881, precision = 0.39%, LOD = 0.4459 mg/l. LOQ = 1.4864 mg/l and for Glibenclamide obtained accuracy = 100.79%, linearity = 0.9993, precision = 0.65%, LOD=0.4372 mg/l, LOQ = 1.4072 mg/l and the MWS method for Metformin HCl obtained accuracy = 100.76%, linearity 0.9949, precision = 0.65%, LOD = 0.9103 mg/l, LOQ = 3.0431 mg/l, and for Glibenclamide with accuracy = 100.07%, linearity = 0.9993. precision = 0.36%, LOD = 0.9205 mg/l. LOQ = 3.0431 mg/l , and appropriate the requirements of ICH guidelines. Conclusion: These Methods successively applied to determine of Metformin HCl and Glibenclamide mixture in tablet dosage form and fulfill the validation requirements.